1988
DOI: 10.3109/03093648809078203
|View full text |Cite
|
Sign up to set email alerts
|

Energy cost of walking with flat feet

Abstract: A comparative study has been conducted to assess the effects of arch support on oxygen consumption in 20 subjects with flat feet who were generally complaining about fatigue, and also to explore whether their feeling of weariness was objective or not. The resting, walking and final recovery heart rates, blood pressures, and walking oxygen consumption values of the patients with flat feet were measured and calculated and compared to a control group using treadmill and oxygen consumption devices. In stage one th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 12 publications
1
28
0
Order By: Relevance
“…However, rather than using "functional" FOs, this study used Sorbothane insoles. Further to this, a positive effect was found by Otman et al (1988) who measured a decrease in oxygen consumption in people with flat feet when they walked with "arch supports".…”
Section: (Vi) Oxygen Consumptionmentioning
confidence: 80%
“…However, rather than using "functional" FOs, this study used Sorbothane insoles. Further to this, a positive effect was found by Otman et al (1988) who measured a decrease in oxygen consumption in people with flat feet when they walked with "arch supports".…”
Section: (Vi) Oxygen Consumptionmentioning
confidence: 80%
“…In this study, the COP-based measures in the ML direction revealed differences between dissimilar foot arches ( Table 6). Previous studies of flat feet have not specifically explored the direction of changes in postural stability [5,[12][13][14]. Among the methods used in these studies, COP-based assessments appear to be the easiest for clinicians to conduct and quantify for use in assessing improvements in, or identifying appropriate management for, individuals with flat feet.…”
Section: Discussionmentioning
confidence: 99%
“…For people with abnormal flat-footed structures, the ability to absorb shock and thus to maintain postural stability is reduced. This may result in inflammation of the plantar fascia, plantar lesions, and body pain, and may even lead to an increased risk of falling [4][5][6][7]. In this way, the structure of the foot arch is important for posture [8], and may be an important variable to assess during pre-participation physical examinations [3,9].…”
Section: Introductionmentioning
confidence: 99%
“…Otman et al [41] reported an 8% decrease in oxygen consumption in flat feet patients when walking with OI. Furthermore, Kavlak et al [40] showed that using OI for 3 months lowered energy expenditure during gait in RA patients.…”
Section: Impact Of Orthoses On Gait Patternmentioning
confidence: 98%